1987
DOI: 10.1243/pime_proc_1987_201_121_02
|View full text |Cite
|
Sign up to set email alerts
|

Prediction of the Decay Process in Turbulent Swirl Flow

Abstract: SwirlJlow in a pipe is studied experimentally and the data so obtained have been compared with theoretical predictions computed from a proposed calculation procedure which determines the swirl intensity, tangential and axial velocity distributions by deJining only the flow pa-ometers ut the inlet of the test pipe.maximum moment of velocity at inlet, yW coefficient, equation (5)

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
8
0

Year Published

1993
1993
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(8 citation statements)
references
References 8 publications
0
8
0
Order By: Relevance
“…Kuroda et al (1981) obtained an approximate equation of axial velocity distribution based on experimental results. Algifri et al (1987) proposed a procedure to compute the swirl intensity, the tangential and axial velocity distributions for given inlet flow conditions. Senoo and Nagata (1972) studied experimentally swirling flow through pipes with different wall roughness and proposed a procedure to compute local wall pressure and average static pressure.…”
Section: Swirling Flow Reviewmentioning
confidence: 99%
“…Kuroda et al (1981) obtained an approximate equation of axial velocity distribution based on experimental results. Algifri et al (1987) proposed a procedure to compute the swirl intensity, the tangential and axial velocity distributions for given inlet flow conditions. Senoo and Nagata (1972) studied experimentally swirling flow through pipes with different wall roughness and proposed a procedure to compute local wall pressure and average static pressure.…”
Section: Swirling Flow Reviewmentioning
confidence: 99%
“…To measure all three components of velocity vector at the measuring point, a probe with three hot wire should be used. However, for swirling flows in the pipe, all researches conducted so far, shown that radial mean velocity is negligible in comparison to the circumferential and axial velocity 1–6,8 . It means that hot‐wire probe with two sensors can be used for valid measurements for this type of flow.…”
Section: Experimental Test Rigmentioning
confidence: 99%
“…In experimental studies of these flows various types of probes and experimental techniques can be used: classical probes, hot‐wire probes, LDA, and in recent years the PIV technique 1–9 . Classical probes are used for the measurement of averaged fields of velocity and pressure.…”
Section: Introductionmentioning
confidence: 99%
“…Results showed that the free swirling flow increases heat transfer rates. Algifri et al [8] proposed a procedure to compute swirl intensity and tangential and axial velocity distributions for given inlet flow conditions. Kitoh [9] experimentally studied the confined swirl flow generated with guide vanes.…”
Section: Introductionmentioning
confidence: 99%